Pendampingan Pencatatan Pembukuan Laporan Keuangan Sederhana Pada Kelompok Usaha Dan Masyarakat Di Kota Payakumbuah, Provinsi Sumatera Barat - Maresti, Dwila (Jurnal Suluah Komunitas, 2023)
This study aims to determine the application of financial records on small and medium business units, to understand the basics and procedures for carrying out simple records and bookkeeping and be able to make financial reports. Tigo Koto Diateh Village is a village in the North Payakumbuh District. The majority of the population in this area work as workers, but the rest of the population are small business actors. However, the increase in business actors was not accompanied by developments in the financial aspect. This is due to the lack of motivation from business actors and the lack of ability of business actors to manage their business finances. Based on observations made by the service team regarding the level of understanding of the training participants, that 80% of the service participants understood the importance of keeping records and simple bookkeeping.